Waarheidsteorieë en interpretasie 1 - Botha, Jan (Koers, 1991)
In this article two theories for the evaluation of the truth of interpretations of ancient written texts arc considered, namely, a correspondence theory of truth and a coherence theory of truth. The author opts for a coherence theory of truth. This choice is motivated by considering these two theories of truth in the context of different and conflicting interpretations of Paul’s Letter to the Romans. The preference for a coherence theory of truth in the context of interpretation is also placed in a broader hermeneutical and philosophical context, reflecting on such issues as foundationalism, fundamentalism, modernity and post-modemity. In the final section, a response is given to a number of issues raised by W.J. Ouweneel.